Bilobalide and PC12 cells: A structure activity relationship study. Issue 2 (15th January 2020) - Usuki, Toyonobu; Yoshimoto, Yukiko; Sato, Makiko; Takenaka, Tae; Takezawa, Ryota; Yoshida, Yusuke; Satake, Masayuki; Suzuki, Noriyuki; Hashizume, Daisuke; Dzyuba, Sergei V.
Graphical abstract: Abstract: Ginkgo biloba extracts have been postulated to beneficial for improving cognitive function and as such they have been used as a potential treatment of Alzheimer's disease. The main active ingredients of the extract are terpene trilactones (TTLs), such as bilobalide (BB) and ginkgolides. Several structure–activity relationship (SAR) studies using ginkgolide scaffolds produced more biologically potent species by modification of the lactone moieties. However, modifications of BB scaffold have been limited, and no SAR studies on BB have been accomplished to date. Thus, the aim of this study was to elucidate how the modification of the lactone moieties of BB would affect their biological activities in a number of assays, including proliferating cell activity, neuroprotective effects against Aβ (1–40) peptides, and neurite outgrowth effects in PC12 neuronal cells. It appeared that the derivatives containing lactone groups showed similar biological activity to native BB, while those that possessed no lactone moieties exhibited lower neurite outgrowth effects. Thus, the results suggested that the lactone moieties of BB played an important role in exerting neurite outgrowth effects in PC12 cells.